Literature review: various statistical analysis in prosocial behavior research - Masya, Hardiyansyah; Lestari, Myrna; Ahman, Ahman; Haka, Nukhbatul Bidayati (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2025)
Humans are social creatures who need and help each other. One of them is by training prosocial behavior in school-aged children and teenagers so that they can create a good social environment, encourage personal development, and increase empathy with others. The broader category of prosocial behavior includes any form of action undertaken or planned to help another person without asking for compensation. This research aims to examine the variety of statistical analyses used in prosocial behavior research over the past five years and to analyze the dynamics of prosocial behavior across different contexts. This research is important because prosocial behavior has a positive impact on both individuals and society as a whole. Through a comprehensive literature review of previous studies, the author identifies a range of statistical methods commonly employed in prosocial behavior research, including regression analysis, path analysis, factor analysis, and multiple linear. The author also discusses the advantages and disadvantages of each statistical analysis method. The results of this research can provide guidance for researchers in choosing appropriate statistical analysis methods to use in prosocial behavior research. In addition, this research can also contribute to the development of the theory and practice of prosocial behavior.